REGENERASI PASARAYA MANGGARAI SEBAGAI RUANG REKREASI DAN KOMERSIAL DENGAN PENDEKATAN TRANSPROGRAMMING - Fauzi, Gilang; Supatra, Suwandi (Jurusan Arsitektur dan Perencanaan, 2024)
City life is now increasingly modern and dynamic, accompanied by advances in digital technology which have caused changes in the lifestyle of city residents. Pasaraya Manggarai is a place that has been affected by this modernization and has experienced significant decline because it is unable to adapt to changing times. The emergence of new and more modern shopping centers resulted in the market starting to lose interest because it could not compete, until finally in 2020 the market stopped operating and the condition of the market is now an abandoned space considered Placeless. The market location holds many memories and is a witness to the development of the Manggarai area, which was once a commercial center until now it has become a major transit area. Therefore, the main objective of this project is to change the face of the Pasaraya into a new commercial and recreational area and maximize Manggarai's potential as a central station. Through the application of contextual methods and transprogramming, it can produce interesting, adaptive and integrated programs with the Manggarai area. In the end, the project will lead to the development of a shopping center, recreation area and cultural education center with a modern touch. The rebuilding of this market is designed to become an attraction in the Manggarai area. Later programs such as Shopping Retail, Game Sports, Communal & Co-Working Space, Reflexology, Hydrotherapy, Bike Park, Bike Exhibition, Interactive Museum, Art Gallery, Exhibition Hall and Public Green Space. This project is expected to become a place to stop, create space for interaction, grow new communities, improve the community's economy and become a new identity for the dynamic Manggrai area. Keywords: Contextual; Placeless; Recreation; Shopping Center; Transprogramming Abstrak Kehidupan kota kini semakin modern dan dinamis dengan diiringi oleh kemajuan teknologi digital yang menyebabkan perubahan gaya hidup masyarakat kota. Pasaraya Manggarai menjadi tempat yang terkena dampak modernisasi ini sehingga mengalami kemerosotan signifikan karena tidak mampu beradaptasi dengan perubahan zaman. Munculnya pusat perbelanjaan yang baru dan lebih modern mengakibatkan pasaraya mulai kehilangan ketertarikan karena tidak dapat bersaing, hingga akhirnya pada tahun 2020 pasaraya berhenti beroperasional dan kondisi pasaraya kini menjadi ruang terbengkalai dianggap Placeless. Titik lokasi pasaraya menyimpan banyak memori dan menjadi saksi perkembangan kawasan Manggarai yang dulu merupakan pusat perniagaan hingga sekarang menjadi kawasan transit utama. Oleh karena itu, tujuan utama proyek ini mengubah wajah pasaraya menjadi area komersial dan rekreasi baru serta memaksimalkan potensi Manggarai sebagai stasiun sentral. Melalui penerapan metode kontekstual dan transprogramming dapat menghasilkan program menarik, adaptif dan terintegrasi dengan kawasan Manggarai. Pada akhirnya Proyek akan mengarah pada pengembangan sebuah pusat perbelanjaan, area rekreasi dan pusat edukasi budaya dengan sentuhan modern, Penmbangunan Kembali pasaraya ini dibuat untuk menjadi atraktor di kawasan Manggarai. Nantinya program seperti Shopping Retail, Game Sports, Communal & Co-Working Space, Reflexology, Hydrotherapy, Bike Park, Bike Exhibition, Interactive Museum, Art Gallery, Exhibition Hall dan Ruang Hijau Publik. Proyek ini diharapkan menjadi tempat singgah, terciptanya ruang interaksi, tumbuhnya komunitas baru, meningkatkan perekonomian masyarakat serta menjadi indentitas baru kawasan manggrai yang dinamis.